Синтез и физико-механические свойства биосовместимых криогелей поливинилового спирта наполненных гидроксиапатитом - Лыткина, Дарья Николаевна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
The influence of establishing the influence of the concentration of PVA and hydroxyapatite obtained in the presence of PVA on the properties of the cryogel of the HA-PVA composite cryogel is considered. As a result of the studies, it was found that the melting temperature and elastic modulus of HA-PVA composite cryogels are affected not only by the concentration of the polymer component, but also by the time of mixing the reaction mixture.